From Local Wisdom to Digital Engagement: Developing Articulate Storyline Media for Contextual Elementary Learning - Quriana, Intan Maulida; Bayan, Umar; Wuryandani, Wuri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop interactive learning media using Articulate Storyline to enhance student interest and learning outcomes in Natural and Social Sciences for elementary education. This study employed a research and development method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The subjects involved were fourth-grade elementary students who participated in media trials and implementation. Instruments used in this study included questionnaires, interview guides, observation sheets, and learning outcome tests. Data collection was conducted through expert validation, limited trials, and classroom application. The analysis utilized descriptive quantitative techniques to determine the media's feasibility, practicality, and effectiveness. Expert evaluations showed that the developed media was appropriate and relevant to the learning content. Responses from teachers and students also indicated that the media was easy to use and engaging. The implementation phase revealed a marked increase in student learning interest, with questionnaire scores rising from 68.5% to 87.2%, and a significant improvement in learning outcomes, as average test scores increased from 72.4 to 85.6 after using the media. The integration of local content based on natural resources in the Special Region of Yogyakarta enhanced the media's contextual relevance and relatability to students. This study contributes to the field of elementary education by offering an innovative and adaptive digital media solution that supports independent and contextual learning, in line with the objectives of the current national curriculum.